Estimating the Role of Roadside Vegetation in Reducing Particulate Matter Pollution in the Karkh District of Baghdad City - AlObaidi, Ammar A. F.; Al-Salman, Ibrahim M. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Baghdad is considered one of the most crowded cities, and it is the location of all government institutions, making it a destination for people from all other provinces. This results in increased traffic density, which in turn leads to increased emissions that contribute to air pollution in the form of gases and particulate matter. This study was conducted from July to December 2022 in the Karkh district of the city, where the Salahuddin highway was divided into five sites based on the presence or absence of plant barriers on either side of the road. PM10 and PM2.5 pollutant concentrations and climatic factors were measured at each site during morning and afternoon peak hours. The study found that concentrations exceeded local and global standards at all sites by several times, posing a real health and environmental risk in the city's atmosphere. The highest concentrations were found at site (E), followed by sites (A) and (D), which were all devoid of plant barriers except for scattered trees. The lowest concentrations were recorded at sites (B) and (C), which contained plant barriers on either side of the road and in median barriers. Although these plant barriers and median barriers did not meet the best standards, they contributed to reducing particulate pollutants by a good percentage compared to the first three sites. Climate factors played a role during the study period, which extended during the summer and winter seasons. Heat and wind speed had a negative correlation with PM10 and PM2.5 concentrations, while relative humidity had a positive correlation. Therefore, from what has been presented, it is necessary to increase the use of public transportation buses for their role in reducing the number of private cars on the street and to focus on planting plants and trees on the sides and in the middle of roads for their role in reducing air and visual pollution and providing natural shade for pedestrians and vehicles.